FORMULASI DAN UJI AKTIVITAS NANO-HERBAL ANTI-HIPERKOLESTEROL DARI KOMBINASI EKSTRAK TEMULAWAK (Curcuma xanthorrhiza Roxb.) DAN SAMBUNG NYAWA (Gynura procumbens (Lour.) Merr.) MENGGUNAKAN MYRITOL 318 SEBAGAI FASE MINYAK - , Indri Meirista ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Extracts of java turmeric (Curcuma xanthorrhiza) and sambung nyawa (Gynura procumbens) with 75:25 ratio was significantly decrease cholesterol levels in hypercholesterolemia rats. Both extracts possess different solubility and low bioavailability. To overcome this problems, java turmeric and sambung nyawa extracts were formulated into self nanoemulsifying drug delivery system (SNEDDS) using myritol oil with various surfactants and co-surfactants. The homogenous formulations were evaluated for extracts loading, emulsification time, size, distribution size, and zeta potential of droplet nanoemulsion, and investigated its anti-hypercholesterol activity towards hypercholesterolemia rats using unmodified extracts, SNEDDS, simvastatin, negative control, and normal groups. Each group were consisted of three randomly selected male wistar rats. Blood cholesterol levels were checked at 0, 15, 30, 45, 60, 67, 75 days and analyzed using ANOVA. The results showed that the optimum SNEDDS formula was consisted of tween 80:tween 20:propylene glycol:myritol 318 (45:15:20:20, %) had extracts loading up to 50 mg/mL with emulsification time around 43.23 seconds, average of droplet size was 17.13 nm and zeta potential was 40.40 Â± 5.44 mV in aquadest, and stable in different pH media. In vivo studies showed that lowering of cholesterol levels of optimum SNEDDS (62.35%) compared to simvastatin (64.57%) were not significantly different (p>0.05), but its significantly different (p<0.05) to unmodified extracts (45.33%) and negative control (46.03%) groups. In conclusion, java turmeric and sambung nyawa extracts SNEDDS using myritol 318 can be proposed as a new alternative of anti-hypercholesterol